2010
DOI: 10.1080/19338240903390362
|View full text |Cite
|
Sign up to set email alerts
|

Manganese, Arsenic, and Infant Mortality in Bangladesh: An Ecological Analysis

Abstract: Recent studies in Bangladesh indicate that arsenic and manganese in tube-well water may increase the incidence of infant mortality. The study reported here examined whether these findings could be replicated. Data available from some 600 villages under the care of the nongovernmental organization (NGO) Gonoshasthaya Kendra included details of 29744 live births and 934 infant deaths in a 2-year period, with age and cause. These were analyzed by mean well levels of arsenic and manganese as reported by the Britis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Pneumonia was given as the most common cause of death at all ages, accounting for 458 deaths. Most deaths assigned to prematurity (N = 262) occurred within the first seven days and most deaths from diarrhoea (N = 50) at ≥29 days [7]. Concentrations of zinc in the 114 individual wells sampled by the BGS in these 12 upazillas ranged from none detected (ND)—0.45 mg/L.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pneumonia was given as the most common cause of death at all ages, accounting for 458 deaths. Most deaths assigned to prematurity (N = 262) occurred within the first seven days and most deaths from diarrhoea (N = 50) at ≥29 days [7]. Concentrations of zinc in the 114 individual wells sampled by the BGS in these 12 upazillas ranged from none detected (ND)—0.45 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Correlations between mean zinc concentration and either arsenic (r = 0.25, p = 0.36) or manganese (r = 0.30, p = 0.28) were low. Information on each of the upazillas is given in Table 1 (which represents a correction from similar data published earlier [7]), from which it can be seen that all-cause deaths/1,000 showed no trend with zinc concentration (high 30.1/1,000: moderate 33.8/1,000: low 31.6/1,000) but that deaths/1,000 from diarrhoea were lower in the high zinc group (0.72/1,000) than in the moderate (2.13/1,000) or low (2.38/1,000). Areas with low zinc tended to have somewhat more births to women of low socioeconomic status or with no education and appeared less likely to be first births.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in sharp contrast with the results from a cross-sectional study, which suggested almost doubling of the risk of spontaneous abortion for women with manganese levels 40.4 mg l À1 in their drinking water, 59 and an ecological study conducted in the US state of North Carolina showing a higher rate of infant mortality in counties with higher manganese concentrations in their drinking water; 60 however, another ecological study conducted in Bangladesh found no association. 61 Therefore, more studies are needed before any definitive conclusions can be made regarding the relationship between fetal or infant mortality and manganese exposure.…”
Section: Birth Outcomesmentioning
confidence: 99%